Health service use among migrants in the German national cohort: the role of birth region and language skills - Wiessner, Christian; Licaj, Sara; Klein, Jens; Bohn, Barbara; Brand, Tilman; Castell, Stefanie; Führer, Amand-Gabriel; Harth, Volker; Heier, Margit; Heise, Jana-Kristin; Holleczek, Bernd; Jaskulski, Stefanie; et al. (International journal of public health, 2024)
Objective: To compare health service use (HSU) between migrants and non-migrants in Germany. Methods: Using data from the population-based German National Cohort (NAKO), we compared the HSU of general practitioners, medical specialists, and psychologists/psychiatrists between six migrant groups of different origins with the utilization of non-migrants. A latent profile analysis (LPA) with a subsequent multinomial regression analysis was conducted to characterize the HSU of different groups. Additionally, separate regression models were calculated. Both analyses aimed to estimate the direct effect of migration background on HSU. Results: In the LPA, the migrant groups showed no relevant differences compared to non-migrants regarding HSU. In separate analyses, general practitioners and medical specialists were used comparably to slightly more often by first-generation migrants from Eastern Europe, Turkey, and resettlers. In contrast, the use of psychologists/psychiatrists was substantially lower among those groups. Second-generation migrants and migrants from Western countries showed no differences in their HSU compared to non-migrants. Conclusion: We observed a low mental HSU among specific migrant groups in Germany. This indicates the existence of barriers among those groups that need to be addressed.